Modified Limberg flap versus modified Karydakis flap in pilonidal sinus disease: single surgeon experience - Turan, Umit (International Surgery Journal, 2019)
Background: The aim of this study was to analyze and compare the results of the modified Limberg flap (MLF) and modified Karydakis flap (MKF) techniques which were performed for the treatment of pilonidal sinus disease (PSD). Methods: The patients who were operated for PSD by the same surgeon between November 2010 and July 2013 in Konya Seydisehir Hospital were retrospectively analyzed. A total of 106 patients were evaluated in this study regarding age, gender, operation time, length of hospital stay, and postoperative complications. Results: There were 14 female and 92 male patients (MLF; 5/52 and MKF; 9/40). MLF was performed in 57 (53.8%) patients and MKF was performed in 49 (46.2%) patients. Length of Hospital stay and drain removal time were less in MKF group but it was not significantly different between two groups (p>0.05). Operation time was shorter in MKF group than MLF group (p<0.05). The complication rates of the MLF and MKF groups were 10.5% and 12.2% respectively. The recurrence was seen in 1 patient in MLF group and 2 in MKF group. Conclusions: MKF has shorter operation time than MLF, however both techniques have a similar complication and recurrence rate. In conclusion MLF and MKF procedures can be safely used as a surgical treatment of PSD.